New thinking in Islam the jihad for democracy, freedom and women's rights - Amirpur, Katajun 1971- (Gingko Library, 2015)
In Rethinking Islam, Katajun Amirpur argues that the West's impression of Islam as a backward-looking faith, resistant to post-Enlightenment thinking, is misleading and-due to its effects on political discourse-damaging. Introducing readers to key thinkers and activists-such as Abu Zaid, a free-thinking Egyptian Qur'an scholar; Abdolkarim Soroush, an academic and former member of Khomeini's Cultural Revolution Committee; and Amina Wadud, an American feminist who was the first woman to lead the faithful in Friday Prayer-Amirpur reveals a powerful yet lesser-known tradition of inquiry and dissent within Islam, one that is committed to democracy and human rights. By examining these and many other similar figures' ideas, she reveals the many ways they reject fundamentalist assertions and instead call for a diversity of opinion, greater freedom, and equality of the sexes.